Embedding Religious Moderation Values through Communication Activities in English Language Teaching - Muthia Farida; Niwayan Sukraini (ENLIT, 2021)
Some reports have uncovered that the number of religious intolerance and violation cases still appear in Indonesia recently. Preventive actions must be taken to keep Indonesia aligned with its national motto “unity in diversity”. This paper discusses the importance of promoting religious moderation toward society to build peace and harmony. Furthermore, this paper addresses the urgency of inserting religious moderation values to school instructions, particularly in English language teaching. Some practical ways of embedding the religious moderation values into English instructions are also presented so that English teachers can apply them in their classes. Finally, it is expected that religious tolerance and respect for diversity can be built among students.